Aspectos oclusais na etiologia das desordenstemporomandibulares - Moreno, Amália [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Brandini, Daniela Atili [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP] (My University, 2012)
Since the occlusion area is presented in almost all specialties of Dentistry, its relationship with the health of the patient has been shown. The etiology of temporomandibular disorders is multifactorial and the occlusion is considered an etiologic factor. This study aimed to discuss the functional occlusion aspects and the presence of temporomandibular disorders. Literature Review: The loss of orthopedic balance can induce temporomandibular disorder. Therefore, both the physiological and functional occlusions have been analyzed as a dental relation. Several functional occlusal factors have been linked to the temporomandibular disorders such as deviations of centric relation to maximum intercuspation, occlusal interferences, absence of posterior teeth, changes on the occlusion vertical dimension, malocclusion, orthodontic treatment and parafunction. Conclusion: The most common occlusal factors related to temporomandibular disorders are quite frequent; however, the diagnosis and treatment of such disorders should be considered individually

A oclusão por estar presente em quase todas as especialidades da odontologia, tem ao longo do tempo mostrado sua relação com a saúde do paciente. A etiologia das desordens temporomandibulares é multifatorial considerando a oclusão como um fator etiológico. Esse trabalho objetivou discutir os aspectos oclusais funcionais e a presença de DTMs. Revisão da Literatura: A desarmonia do equilíbrio ortopédico pode ocasionar a desordem temporomandibular. A partir de então, a oclusão fisiológica ou funcional vem sendo analisada na relação dental. Entre os fatores oclusais funcionais analisados com maior relação às desordens temporomandibulares têm-se os devios de relação central para máxima intercuspidação habitual, interferências oclusais, ausência de dentes posteriores, alteração na dimensão vertical de oclusão, má-oclusão e tratamento ortodôntico, e parafunção Conclusão: Os fatores oclusais mais relacionados às disfunções temporomandibulares são bastante freqüentes, devendo, no entanto o diagnóstico e o tratamento ser analisado individualmente.
Occlusal aspects related to the etiology oftemporomandibular disorders
Keywords: Dental occlusion; Temporomandibular disorders; Centric relation; Centric occlusion; Occlusal interference; Dor facial; Síndrome da disfunção da articulação temporomandibular; Diagnostico bucal; Relação central